Simulation of main plasma parameters of a cylindrical asymmetric capacitively coupled plasma micro-thruster using computational fluid dynamics - Greig, Amelia; Charles, Christine; Boswell, Roderick W. (Frontiers in Physics, 2015)
Computational fluid dynamics (CFD) simulations of a radio-frequency (13.56 MHz) electrothermal capacitively coupled plasma (CCP) micro-thruster have been performed using the commercial CFD-ACE+ package. Standard operating conditions of a 10 W, 1.5 Torr argon discharge were used to compare with previously obtained experimental results for validation. Results show that the driving force behind plasma production within the thruster is ion-induced secondary electrons ejected from the surface of the discharge tube, accelerated through the sheath to electron temperatures up to 33.5 eV. The secondary electron coefficient was varied to determine the effect on the discharge, with results showing that full breakdown of the discharge did not occur for coefficients less than or equal to 0.01.